The Role of Bhabinkamtibmas through Counseling in Reducing the Theft under Aggravated Circumstances Rate: Case of Ciamis Police Department - Nikodemus Wospakrik (Advances in Police Science Research Journal, 2020)
This research is motivated by the increasing number of theft by weighting criminal in Ciamis District. The high level of community activities in Ciamis Subdistrict makes the criminal acts that occur getting higher. This thesis is written with qualitative approach and adopting descriptive research. Collecting data techniques with interviews, observations, and document review. There are primary and secondary data sources, and the theories used to analyze the problems are management theory and role theory. The results of the research found that the role of Bhabinkamtibmas in preventing criminal of two-wheeled ride was carried out through coaching Bhabinkamtibmas. While the efforts made by Bhabinkamtibmas are through counseling activities. There are several factors that influence Bhabinkamtibmas in carrying out their duties, such as internal factors which is consist of human resources, facilities and infrastructure factors, and Money factors while external factors come from the community itself. Based on the discussion of the study the authors advise the leadership to conduct analysis and evaluation toward these Bhabinkamtibmas and have a standard for assessing members of Bhabinkamtibmas. And also improving competence of Bhabinkamtibmas through training, emphasizing the provision of material to the public regarding the theft of two-wheeled vehicles, improving suggestions and infrastructure owned by the Ciamis Police Station, as well as providing rewards and punishment to members of Bhabinkamtibmas as motivating at work.